Cinema e cidade: mobilidade, oralidade e precariedade no cinema de Ozualdo Candeias (1967-92) - Teles, Angela Aparecida (2006)
This thesis interprets the São Paulo built through images by the film maker Ozualdo Candeias from 1967 to 1992 as a problematization of the exchanges held at the frontier between the urban world and the rural one, born from the process of industrialization and urbanization intensified in the fifties. By means of the creation of a Esthetics of Precariousness, the film maker invented cinematographic procedures for narrating the process of unstructuring of the paulista rural world on its meeting with the city. The geographic and cultural disterritorialization and the movement of reconstitution and resignifying of new territories in the city were aesthetically constructed through the mobility and orality of the rural populations received by the city, as well as the urban precariousness received by the country. In the chapter Cinema and Memory: Candeias at the Trash Point, we discuss the historical experience of the Cinema at the Boca do Lixo and its importance for the trajectory of Candeias as a city resident as well as a movies director. Starting from the fragments of memory registered in published statements, from the photos and documentaries on the Boca Cinema , we interpret the meanings which the director attributed to the rua do Triunfo (Triumph Street) as a social space for the movies people , and for some other sociabilities that anchored their existences in that street and neighborhood. In the chapter São Paulo, between the rural and the urban, we interpret the cinematographic representation of the process of disterritorialization and reterritorialization of the countryman in the city, interlaced with the experience of the cultural dislocation also lived by Candeias. In the chapter An Esthetics of Precariousness, we work the elements of what we named as the Esthetics of Precariousness: the mobility, the orality, and the precariousness esthetically worked out by means of the mixing up of fiction and documentary, of the disconstruction of classical cinema clichés based on photogeny, diegesis, scenery, characters and editing